Medieval art and architecture in the diocese of Glasgow
1 online resource
Keywords: This volume includes many of the papers given at the 1997 conference of the British Archaeological Association. It focuses on aspects of patronage, the wider architectural context of the cathedral, and on the Romaneque sculpture and manuscripts with the diocese.